2021
DOI: 10.1186/s13020-021-00510-6
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin attenuates rheumatoid arthritis by targeting SOCS1/JAK/STAT signaling pathway of fibroblast like synoviocytes

Abstract: Background Rheumatoid arthritis is a progressive and systemic autoimmune disease seriously compromises human health. Fibroblast like synoviocytes are the major effectors of proliferation and inflammation in rheumatoid arthritis synovial tissue. Shikonin has anti-inflammatory and immunomodulatory activities. But, its role on synovitis of rheumatoid arthritis is unknown. Methods The DBA/1 male mice were randomly divided into the following three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…RA-FLS invasive characteristics are related to a series of pathological processes, such as overproliferation, release of proinflammatory mediators, interactions with immune and nonimmune cells, direct or indirect joint destruction [27][28][29]. It is demonstrated that lipid metabolism can promote breast cancer stemness and chemoresistance [19].…”
Section: Discussionmentioning
confidence: 99%
“…RA-FLS invasive characteristics are related to a series of pathological processes, such as overproliferation, release of proinflammatory mediators, interactions with immune and nonimmune cells, direct or indirect joint destruction [27][28][29]. It is demonstrated that lipid metabolism can promote breast cancer stemness and chemoresistance [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Chikusetsusaponin IVa targets the JAK/STAT signaling pathway to exhibit anti‐inflammatory and osteoprotective effects in RA 28 . Shikonin modulates the SOCS1/JAK/STAT signaling pathway to improve RA progression 29 . Besides, lncRNA ZNF667‐AS1 accelerates the JAK/STAT pathway to alleviate RA progression 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed histopathological scores of arthritis severity were blindly measured by experimenters as described in our previous study. 10 …”
Section: Methodsmentioning
confidence: 99%
“…After the mice were euthanized, the joints, lungs, livers, kidneys, and serum of the mice were harvested for H&E staining, immunofluorescence, immunohistochemistry, and enzyme‐linked immunosorbent assay (ELISA). Detailed histopathological scores of arthritis severity were blindly measured by experimenters as described in our previous study 10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation